2016
DOI: 10.1186/s11671-016-1662-8
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Properties of Rutile TiO2 Nanorod Array in Lithium Hydroxide Solution

Abstract: In this paper, rutile TiO2 nanorod arrays are fabricated by a template-free method and proposed as a promising anode for aqueous Li-ion battery. The as-prepared TiO2 nanorod arrays exhibited reversible Li-ion insertion/extraction ability in aqueous LiOH electrolyte. Moreover, galvanostatic charge/discharge test results demonstrated that the reversible capacity of TiO2 nanorods could reach about 39.7 mC cm−2, and 93.8 % of initial capacity was maintained after 600 cycles at a current density of 1 mA cm−2 (=240 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Since lithium ions are more easily transported along the c -direction [ 134 , 135 ], rutile TiO 2 can improve the electrochemical performance by adjusting the growth direction of nanoarrays [ 136 , 137 , 138 ]. The c -direction TiO 2 nanorod arrays displayed outstanding cycling performance, with 93% capacity containing after 600 cycles [ 139 ]. Similarly, Dong et al also prepared rutile TiO 2 nanorod arrays growing along the direction of the c -axis.…”
Section: Energy Storage Applications Of Nanostructured Tio ...mentioning
confidence: 99%
“…Since lithium ions are more easily transported along the c -direction [ 134 , 135 ], rutile TiO 2 can improve the electrochemical performance by adjusting the growth direction of nanoarrays [ 136 , 137 , 138 ]. The c -direction TiO 2 nanorod arrays displayed outstanding cycling performance, with 93% capacity containing after 600 cycles [ 139 ]. Similarly, Dong et al also prepared rutile TiO 2 nanorod arrays growing along the direction of the c -axis.…”
Section: Energy Storage Applications Of Nanostructured Tio ...mentioning
confidence: 99%
“…TiO 2 has been studied for application in large-scale energy storage because it is a high-capacity and high-current rate tolerance material [8,50,51]. It has various nanostructure forms, such as nanorods, nanotubes, nanofibers and nano squares.…”
Section: Electrophoretically Deposited Graphene and α-Fe 2 O 3 /Tio 2mentioning
confidence: 99%
“…The use of nanostructured TiO 2 -based materials may be an efficient approach to deal with the main problems of Li-ion batteries [50,51].…”
Section: Electrophoretically Deposited Graphene and α-Fe 2 O 3 /Tio 2mentioning
confidence: 99%
“…Numerous commercially available Li ion intercalated materials such as LiCoO 2 , LiMn 2 O 4 , LiFePO 4 , LiMnPO 4 , and LiNi 1/3 Co 1/3 Mn 1/3 O are efficiently performing cathode materials for ARLB. The various reported anode materials such as oxides (VO 2 (B), layered γ-LiV 3 O 8 , H 2 V 3 O 8 , V 2 O 5 , and TiO 2 ), polyanionic compounds (TiP 2 O 7 and Na super ionic conductor (Nasicon)-type LiTi 2 (PO 4 ) 3 ), and organic compounds (polypyrrole and polyamides) redox reaction of which are in a narrow potential window of hydrogen evolution. On the basis of earlier studies, a majority of anode materials demonstrated significant capacity fading during galvanostatic charge–discharge cycling along with limited discharge capacity when compared to LIB.…”
Section: Introductionmentioning
confidence: 99%